Enhancement Of ZnO-Based UV Photodetectors By Incorporating Bi₂O₃, Ag, And Ge Nanostructures Synthesized Using Laser Ablation In Liquid - Marzouq B.,, Alharbi Abdullah (2025)
This research enhances the efficiency of UV photodetectors through the synthesis and integration of nanoparticles using laser ablation techniques. The study investigates the effects of bismuth oxide nanosheets (Bi2O3-Nsh), silver nanoparticles (AgNPs), and germanium nanowalls (GeNWs) on ZnO/Si-based UV photodetectors.